Issues and Concerns of Sugarcane in Uttar Pradesh: Analyzing the issues and concerns of sugarcane in Uttar Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Recently, the Union government approved an Rs. 6,000-crore interest-free loan to the sugarindustry to clear cane arrears to farmers at Rs. 21,000 crores. Sugar mills will prepare a list of farmerswhose dues they must clear, and banks will transfer the amount to the Jan Dhan accounts of canegrowers. The Cabinet Committee on Economic Affairs also decided that the loans be given to units thatcleared at least 50 per cent of their arrears before June 30. This is the Centre's second time issuing aninterest-free loan to millers to clear arrears. In December 2013, the government gave an interest-free loanof Rs. 6,600 crore.The Indian Sugar Mills Association said this did not address the basic problem of surplus sugar anddepressed prices. The industry, which is demanding the creation of a two million-tonne buffer stock ofsugar on government account to reduce stocks, a government agency like the FCI or MMTC, STC orAPEDA could instead buy out 2.5-3 million tonnes of surplus sugar from the industry to help it reducestocks and pay up the farmers.Union Minister told journalists after the Cabinet meeting that the Centre had already taken severalmeasures, including an increase in sugar import duty to 40 per cent, raising export subsidy on raw sugarand an increase in ethanol prices to promote its blending with petrol.There are diverse views of the Union government and the sugar industry, and both are correct in theirsense. But the issue is that problems faced by farmersgrowers of sugarcane are not ending. One shouldhave to look deeply into this concern. The present report analyses the issues and concerns related tosugarcane in Uttar Pradesh, where there is a significant potential to produce sugarcane and sugar. Thereport contains the whole scenario of sugarcane in India, especially in Uttar Pradesh and its relatedproblems. Uttar Pradesh, the largest producer of sugarcane, should be deeply examined in case ofincreasing sugar surplus with rising cane arrears and their problems so that policy making could bemade more effective and help the farmers and mill owners get rid of their problems.